Collective Bargaining and Police Misconduct: Evidence from Florida - Dhammika Dharmapala; Richard H. McAdams; John Rappaport (Center for Economic Studies and ifo Institute (CESifo), 2019)
Growing controversy surrounds the impact of labor unions on law enforcement behavior. Critics argue that unions impede organizational reform and insulate officers from discipline for misconduct. Yet collective bargaining tends to increase wages, which could improve officer behavior. We provide quasi-experimental empirical evidence on the effects of collective bargaining rights on violent incidents of misconduct. Our empirical strategy exploits a 2003 Florida Supreme Court decision (Williams), which conferred collective bargaining rights on sheriffs' deputies, resulting in a substantial increase in unionization among these officers. Using a Florida state administrative database of “moral character” violations reported by local agencies between 1996 and 2015, we implement a difference-in-difference approach in which police departments (which were unaffected by Williams) serve as a control group for sheriffs' offices (SOs). Our estimates imply that collective bargaining rights led to a substantial increase in violent incidents of misconduct among SOs, relative to police departments. The effect of collective bargaining rights is concentrated among SOs that subsequently adopted collective bargaining agreements, and the timing of the adoption of these agreements is associated with increases in violent misconduct. There is also some evidence consistent with a “bargaining in the shadow” effect among SOs that did not unionize.
Keywords: J45; J50; K42; 330; collective bargaining rights; police unions; police misconduct; law enforcement